The Characteristics and Analysis of the Economic Cycle in Lithuania - Barkauskaitė, Aida; Eglinskaitė, Vaida (Jaunųjų mokslininkų darbai, 2015)
Changes in economic performance, unstable economic growth are the characteristics of the economic cycle. The phases and characteristics of the economic cycle have been analyzed by such researchers as Štreimikienė and Ramanauskienė (2012), Berthoud and Sosa (2011), Rosier (2003), Fanning (2007), Bormotov (2009), Mackevičius (2012), etc. but scientific literature on the characteristics of Lithuania‘s economic cycle has been lacking. The aim of this research is to analyze the characteristics of Lithuania‘s economic cycle and the impact of the country‘s economic indicators on its construction sector during 1999-2013. Analysis of economic indicators shows the phase of the economic cycle a country‘s economy is in: expansion or contraction, peak or trough. These phases are characterized by changes in production, employment rate, consumption, investment, incomes, etc. Economic indicators are monitored and regularly analyzed, measures are taken depending on the duration of the phase, its impact on a country‘s economy, etc. Analysis of a set of economic indicators allows to evaluate the state of a country‘s economy. Analyzing Lithuania‘s economic indicators during 19992013, it was found that from 1999 until 2007 the country‘s economy was in the growth phase, from 2007 until 2010 there was a decline in GDP and domestic consumption and a rise in unemployment but from 2010 until 2013 the country‘s economy showed the signs of recovery and growth. Analyzing the performance of the construction sector during the same period, it was found that in 2009 the sector encountered major difficulties and reached the lowest level. Economic forecasts allow to say that the construction sector will grow. Economic indicator analysis helps better prepare for difficult times and soften negative impacts therefore they should be regularly analyzed.